Studi Kasus Pemberian Edukasi Feeding Rules terhadap Peningkatan Pengetahuan Ibu dengan Anak Stunting di Desa Banteran - Hasna, Tsabitah; Ramawati, Dian (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Background: Stunting is a growth and development disorder experienced by children due to poor nutrition, recurrent infections and inadequate psychosocial stimulation. One of the important factors that influences the nutritional status of children under five is the mother's knowledge about nutrition in children under five. Mothers' knowledge regarding toddler nutrition can be increased through health education. One health education that can be given to mothers with stunting toddlers is the implementation of feeding Methods: This research is a type of qualitative research with a case study approach. The first stage carried out in this research was conducting an assessment and providing implementation based on the articles found, namely providing education on feeding rules. Pre and post-test evaluations are carried out to measure increased knowledge. Results: Implementing feeding rules education can increase mothers' knowledge of stunting toddlers. This is proven by an increase in mother An's knowledge. A during the pre-test the results were 53.3% (poor) to 100% (good). The same thing happened to Mrs. An. D experienced an increase in knowledge from 46.6% (poor) to 100% (good). Conclusion: Education on feeding rules can increase knowledge among mothers of stunted toddlers